Claims-Makers Versus Non-Issue-Makers: Media and the Social Construction of Motorcycle Ban Problems in China - Xu, Jianhua (Qualitative Sociology Review, 2015)
In the past decade, more and more cities in China have adopted policies to ban motorcycles in the name of crime prevention or modernization. This paper examines the differential role of mass media in the construction of motorcycle ban policies in Southern China in general, and in the city of Guangzhou in particular. Although Guangzhou was neither the first city to ban motorcycles nor the city adopting the most radical means of implementing this policy, the media have successfully constructed a social problem of banning motorcycles in Guangzhou. Using content analysis of newspaper articles, I found that from 2000 to 2009 nearly two thirds of newspaper reports on motorcycle ban policy in China were published by newspapers based in Guangzhou. I argue that the relatively liberal media in Guangzhou played a vital role in constructing the ban policy as a social problem. In addition, I examine media discourse in constructing the problem of motorcycle ban policy and argue that although the mass media are still under strict control and serve as mouthpiece of the Chinese Communist Party-State, their increasing commercialization has made it possible to work as claim-makers for a social problem in China.